Fruit quality in Hass avocado and its relationships with different growing areas under tropical zones - Henao-Rojas, Juan Camilo; Horacio Lopez, Jaime; Walter Osorio, Nelson; Ramírez-Gil, Joaquín Guillermo (Revista Ceres, 2025)
Avocado is currently an important crop in Colombia, given its growth in planted area and the increase in exports. The destination market of Colombian avocado is mainly international, and its quality is outstanding. However, the physical and chemical characteristics associated with the quality of the avocados produced are not currently well known in Colombia. The aim of this study was to evaluate the physical, chemical and nutritional parameters associated with the quality of Hass avocado in eight localities of the department of Antioquia based on descriptive statistics. Additionally, the quality was related to the localities through a multivariate analysis. As a result, quality at preharvest parameters of Hass avocados cultivated in Antioquia is similar or superior to that reported internationally based on physical and chemical variables. In addition, a relationship was established between the quality of fruits and the plots where these were cultivated, which allowed discriminating fruits by their region of origin. This work shows an approach to the determination of quality parameters in Hass avocado in Colombia and how they can be related to the characteristics of its productive system, which can lead to defining a product with added value.